A global review of chromosome number and genome size for the filmy ferns family (Hymenophyllaceae, Polypodiopsida) - Fernanda Pessi de Abreu; Felipe Gonzatti; Isabela Andrade Bahima; Tatiana Teixeira de Souza-Chies; Eliane Kaltchuk-Santos (Rodriguésia, 2024)
Abstract Hymenophyllaceae is a fern family comprising around 450 species distributed among nine genera. Genome size and chromosome number have been recurring research target for Hymenophyllaceae in taxonomic and evolutionary studies. However, there is currently a lacks a thorough compilation for this information. The objective of this study was to compile data on chromosome number and genome size for Hymenophyllaceae. A panorama was constructed in order to highlight the observed patterns for the genera and subgenera. The discussed topics also included the geographic areas sampled and the methodological challenges surrounding data acquisition. This study included data on chromosome number and genome size for 158 and 15 species. The family displayed great variation for these characteristics, ranging from 2n = 22 to 356 for chromosome number and from 2C = 21.47 pg to 73.2 pg for genome size. The genera Callistopteris, Polyphlebium, Vandenboschia, Crepidomanes and Hymenophyllum have 2n = 72, or multiples of this value, as the most frequent numbers, Trichomanes and Cephalomanes mainly have 2n = 64 (or multiples), and Didymoglossum has mostly 2n = 68 (or multiples). We hope that this review will assist in the development of future research, seeking a better understanding of evolution and taxonomy for the Hymenophyllaceae.